STUDY ON DOUBLE-EFFECT DISTILLATION PROCESS FOR SEPARATING METHANOL-WATER USING ASPEN PLUS V10 - Zauziah Pramiswari Putri; Cucuk Evi Lusiani; Zhang Zhishan (DISTILAT: JURNAL TEKNOLOGI SEPARASI, 2022)
Methanol (also known as CH3OH, methyl alcohol, hydroxymethane, wood alcohol, or carbinol) is a widely used primary raw material. It is one of the first organic chemicals to find extensive laboratory and industrial use. Methanol and water are ideal binary systems that can be separated by conventional distillation. This study aims to separate methanol-water using a simulated double-effect distillation process in Aspen Plus. To obtain a higher purity of methanol and consider the high energy consumption of the distillation process, double-effect distillation with a double column was used. Furthermore, the single-column and double-effect distillation processes can be simulated by Aspen Plus software. The software version used in this simulation is Aspen Plus V.10 with NRTL thermodynamics methods as binary interaction parameters. The double effect distillation column was equipped with a heat exchanger, splitter, and pump. Moreover, a design specification is needed to get the purity of methanol as wanted. Compared to each column process, the temperature profile of each column process is directly proportional to the number of stages. By simulation process that has been carried out, the purity of methanol in the single-column process and double-effect distillation process is slightly different with 97.1% and 97.2%, respectively. In the double-effect distillation process, columns C1 and C2 save 0.6% and 0.37% of energy in the single-column process, respectively. It indicates that the double-effect distillation has obvious advantages over single-column distillation in terms of purity of methanol and energy saving.